(untitled) (Dermatology Reports, 2025)
Dear Editor, Atrophic lichen sclerosus (ALS) is a chronic inflammatory dermatosis with significant morbidity, primarily affecting genital areas. The disease is often misdiagnosed or underdiagnosed, resulting in delayed treatment and progression to atrophic stages and permanent scars. While corticosteroids remain the first-line treatment, their long-term use may lead to adverse effects such as skin atrophy, prompting the need for alternative therapies. Cyclosporine, a calcineurin inhibitor, has shown efficacy in managing immune-mediated skin diseases and is delivered effectively through the Pentravan® vehicle. [...]